Study On Productivity Improvement Of Low Permeability Gas Reservoir By Hydraulic Fracturing - Usman Usman; Darsono Marino; Marzuki Soelistijono (Scientific Contributions Oil and Gas, 2010)
The C5 well completed in the LZ tight gas limestone reservoir of C field is considered very good candidate for stimulation by hydraulic fracturing for the following reasons. The reservoir gross thickness of 127 ft is thick enough. Long fractures can be created. Penetrated zone is far from lowest known gas. The permeability of 0.2973 mD and the absolute open flow potential of 2.3 MMscf are low. Estimated proven gas accumulation of 24.5 Bscf is significant. Crosslinked Gel + Hi Temp Stabilizer is used as fracturing fluid due to high temperature reservoir of 334oF. High-strength of Sintered Bauxite proppant with 20/40 mesh sand is selected for this high stress formation of reservoir rock. The desired propped fracture width is 0.1004 inch. The fracture height is approximately 62.5 ft based on the half height from the centre depth of reservoir upward and downward. The propped fracture halflengths are predicted by Perkins-Kern-Nordgren model. Prediction shows that to have the propped fracture half-gths of 1335, 1587, 1850, 2114, 2356, 2576 and 2640 ft for the propped fracture width of 0.1004 inch and the fracture height of 62.5 ft, the required proppant weight in one fracture wing are 139,167,195,221, 246, 271 and 278 Mlbs respectively. With the obtained propped fracture halflengths, the productivities improvement (J/Jo) are 13.8, 16.4, 19.2, 21.9, 24.4, 26.7 and 27.3